KOMPETENSI PEDAGOGIK GURU PAI DALAM MENGHADAPI SISWA BERKEBUTUHAN KHUSUS PADA KELAS INKLUSI DI SD NEGERI RANDUPITU - Cahyaning Harum Pramudya, Sendhika; Kirom , Askhabul; Fachrudin Yusuf, Wiwin; M. Jamhuri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze and describe the pedagogical competencies of Islamic Religious Education (IRE) teachers in handling students with special needs in inclusive classrooms at Randupitu Public Elementary School. This study employs a qualitative approach using a descriptive research design. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis utilized Spradley’s model, which encompasses domain, taxonomic, component, and cultural theme analyses, with data validity tested through credibility, transferability, dependability, and confirmability. The results indicate that the teachers’ pedagogical competencies in Islamic Education have been adaptively applied across three main aspects: planning, implementation, and evaluation of learning. During the planning phase, teachers mapped student characteristics, modified learning objectives, and prepared multisensory learning materials. During the implementation phase, teachers employed creative methods such as singing, using multimedia technology, providing additional support, and ensuring flexibility in the learning environment. During the evaluation stage, teachers use process-based assessment, provide accommodations during exams, and adjust graduation standards for students with special needs.These findings indicate that the success of inclusive learning depends heavily on teachers’ ability to adapt instructional strategies to students’ needs, thereby creating a learning process that is fair, humane, and effective.